2014
DOI: 10.1136/amiajnl-2014-003023
|View full text |Cite
|
Sign up to set email alerts
|

Implications of an emerging EHR monoculture for hospitals and healthcare systems

Abstract: In many hospitals and health systems, a 'new' electronic health record means a shift to one vendor: Epic, a vendor that dominates in large and medium hospital markets and continues its success with smaller institutions and ambulatory practices. Our paper examines the implications of this emerging monoculture: its advantages and disadvantages for physicians and hospitals and its role in innovation, professional autonomy, implementation difficulties, workflow, flexibility, cost, data standards, interoperability,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
89
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 121 publications
(94 citation statements)
references
References 2 publications
4
89
0
Order By: Relevance
“…The results showed that, while it is technically possible to convert data between these formats, the transformation is ''lossy'' as these formats were created for different purposes and have unique structural differences which inhibit data conversion. Koppel and Lehmann (2015) 23 In the absence of data standards that enable data to be exchanged among eHR systems, one of the advantages of a monopolistic system is a ''de facto establishment of data standards. ''…”
Section: Number Of Companiesmentioning
confidence: 99%
“…The results showed that, while it is technically possible to convert data between these formats, the transformation is ''lossy'' as these formats were created for different purposes and have unique structural differences which inhibit data conversion. Koppel and Lehmann (2015) 23 In the absence of data standards that enable data to be exchanged among eHR systems, one of the advantages of a monopolistic system is a ''de facto establishment of data standards. ''…”
Section: Number Of Companiesmentioning
confidence: 99%
“…We must also acknowledge that cognitive dissonance makes recognition of unintended consequences hard to see. Hospital personnel spend up to five years and sometimes billions of dollars with the implementation process [11]. Careers and budget justifications are on the line for such massive investments.…”
Section: Introductionmentioning
confidence: 99%
“…We selected this patient portal for study as Epic is replacing other vendors in the EHR market and is beginning to establish a single vendor landscape. Reportedly, Epic has at least partial health information for over 51% of the US population [36]. MyChart mobile app is available for Apple and Android devices.…”
Section: Data Collection and Preparationmentioning
confidence: 99%